Do Land Rights Unlock Women’s Participation? Insights from Smallholder Farming in Mbeere South, Kenya - Alexander Njue Muthee; Nason Vundi; Antony Wando Odek (Research Parks Publishers, 2026)
Women provide most of the labor in smallholder farming, yet their control over land remains limited. riculture is done by women while their ownership of land is constrained. This research sought to establish the relationship between the rights to land and women's in. It specifically focused on land access, ownership documentation, control over farming decisions, and awareness of legal rights. Using a descriptive, mixed-methods design, 310 women were sampled from a population of 1,562 through stratified and simple random sampling. Data came from questionnaires, key informant interviews, and focus groups. Quantitative data were analyzed with descriptive statistics, cross-tabulations, and ordinal regression; qualitative data were analyzed thematically. Results show 60.2% of women had full land access, but only 5.5% had sole ownership. All women with full rights awareness and 80.7% of independent decision-makers had high participation. Significant associations were found (χ² up to 53.074, p < 0.01). Regression results highlight that limited decision-making (β = -1.605, p = 0.005) and low rights awareness (β = -18.762, p < 0.001) reduce participation. The study finds that secure land rights, decision-making autonomy, and knowledge of entitlements strongly shape engagement, while gaps in control and awareness keep many women from fully participating in farming.